Fighting Social Isolation With Nostalgia: Nostalgia as a Resource for Feeling Connected and Appreciated and Instilling Optimism and Vitality During the COVID-19 Pandemic - Puente-Díaz, Rogelio; Cavazos-Arroyo, Judith (Frontiers in Psychology, 2021)
In two experiments, we tested the influence of bringing to mind a memory of a special moment versus an ordinary moment on nostalgia and whether this elicited nostalgia was related directly to gratitude and the satisfaction of need for relatedness and indirectly to optimism and vitality. Participants from Mexico were first asked to state how the pandemic of COVID-19 has affected their lives. After, participants were randomly assigned to one of two conditions: Memory of special moment versus memory of ordinary recent moment (study 1) or memory of special moment versus or memory of ordinary moment from the same life period as the special moment (study 2) and completed a battery of questionnaires assessing nostalgia, gratitude and optimism (study 1) or nostalgia, satisfaction of need for relatedness, and vitality (study 2). Results from study 1 showed a positive influence of bringing to mind a special moment on nostalgia. Nostalgia was positively related to gratitude, which was then related positively to optimism. Similarly, results from study 2 showed a positive influence of bringing to mind a special moment on nostalgia. Nostalgia was positively related to satisfaction of need for relatedness, which then had a positive relationship with vitality. In both studies, the indirect sequential effect of bringing to mind a special moment on optimism and vitality was significant.